Crowdfunding sebagai Bentuk Budaya Partisipatif pada Era Konvergensi Media: Kampanye #BersamaLawanCorona (Kitabisa.com) - Dhyayi Warapsari (Avant Garde, 2020)
The internet and digital technology provide convenience for humans to carry out various activities that were originally carried out manually, face-to-face, and with time and distance limitations. With new technologies in the digital age connected to the internet, people can easily connect to each other even though separated by distance. However, all of these technologies are meaningless without humans as users. The existence and usefulness of technology depends on the institution and culture that enable the technology to survive so that it is important to study the participatory culture that surrounds the technology. There are four forms of participatory culture that can be studied, namely affiliations, expressions, collaborative problem-solving, and circulations. One of the problems being faced by Indonesia in 2020 is the Covid-19 pandemic issue. The increasing number of people diagnosed positive for Covid-19 and the death toll has caused panic among the people so that many people buy medical devices, such as masks and hand sanitizers, for prevention. It causes a shortage of stocks and a sharp increase in prices for medical devices, whereas medical personnel who directly deal with patients urgently need it. In the midst of financial difficulties to prevent and overcome the spread of Covid-19, a #BersamaLawanCorona fundraising campaign was launched by the crowdfunding platform Kitabisa.com in collaboration with several partners. This paper is a conceptual paper with a qualitative literature review method that attempts to build an argument for a logical relationship between the concepts of crowdfunding, participatory culture, and media convergence in the context of #BersamaLawanCorona fundraising campaign organized by Kitabisa (Kitabisa.com) that help resolve the Covid-19 pandemic problem in Indonesia.